A Review on Macroscopy, Microscopy and Pharmacological Activity of Cayratiatrifolia Linn. - Sharma, Kapil; Salvi, Lavish; Gupta, Ravi; Meghani, Monika; Nagar, Pradhuman Kumar; Dubey, Chetan Kumar; Nagar, Jagdish Chandra (Asian Journal of Pharmaceutical Research and Development, 2020)
Cayratiatrifolia (Linn.)Domin is a perennial climber, family Vitaceae, found in India, Asia and Australia. The plant is found in hilly regions as well as the hotter part of India from Jammu and Rajasthan to Assam. It is commonly known as fox grape in English, Amalbel, Ramchana in Hindi and Amlavetash in Sanskrit. The plant has trifoliated leaves with (2-3cm) long petioles and ovate to oblong-ovate leaflets. Flowers are small greenish white and brown in colour. Fruits are fleshy, juicy, spherical, about 1 cm in diameter of dark purple or black colour.The stem composed of cork cells on the outer side and composed of small size sclerenchymatous cells. The cortex is wide and has parenchymatous cells. Numbers of sclereids are widely distributed in the cortex region. Cortex also shows the presence of calcium oxalate crystals.The leaf surface shows the stomata covered with guard cells followed by epidermis layer (Figure2A). Epidermal cells are rectangular, thin and straight walled cells. Stomata are anisocytic or unequal celled stomata, three subsidiary cells, one is smaller than other two. Leaf surface analysis also shows the presence of veins, vein islet and vein termination (Figure2B). Transverse section of leaf shows the epidermis layer followed by cuticle layer and vascular bundles (xylem and phloem).The leaf powder is pale green in color, with a characteristic odour and bitter taste.This plant also contains kaempferol, myricetin, quercetin, triterpenes and epifriedelanol. Whole plant of Cayratiatrifolia has been reported to contain yellow waxy oil, steroids/terpenoids, ﬂavonoids, tannins. Plant shows the antioxidant, antidiabetic, antibacterial, antiviral and anticancer activity.